Synthesis of NiFe₂O₄ Magnetic Using Artocarpus altilis Leave Extract for Photocatalytic Degradation of Methylene Blue Dye and Antibacterial Applications - Bella Safitri; Heni Yohandini; Muharni Muharni; Salni Salni; Poedji Loekitowati Hariani (Jurnal Kimia Sains dan Aplikasi, 2024)
The green synthesis method is an economical and eco-friendly approach to synthesizing materials. This study effectively synthesized magnetic NiFe2O4 by Artocarpus altilis extract leave for the photocatalytic degradation of Methylene blue dye and exhibited antibacterial properties. The phytochemical compounds found in plants act as agents for reducing and stabilizing NiFe2O4. The synthesized NiFe2O4 was examined using X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), ultraviolet-visible diffuse reflectance spectroscopy (UV-DRS), and vibrating sample magnetometry (VSM). The variables in degradation include solution pH, dye concentration, catalyst dose, and irradiation time. The synthesized NiFe2O4 has a 12.4 nm crystallite size, a saturation magnetization (Ms) of 44.56 emu/g, and a band gap of 1.68 eV. The degradation efficiency of methylene blue dye was 98.2% under the following conditions: a solution pH of 10, a concentration of 10 mg/L, a dose of 0.1 g/L, and an irradiation time of 90 min. The degradation mechanism of Methylene blue dye may be accurately described by pseudo-first-order kinetics, with a kapp value of 0.0443 min-1. NiFe2O4 has high stability; after five degradation cycles, the degradation efficiency decreased by 4.45%. Additionally, NiFe2O4 demonstrates significant antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria.